Daphnetin inhibits high glucose-induced extracellular matrix accumulation, oxidative stress and inflammation in human glomerular mesangial cells - Ke Xu; Liqin Guo; Haixia Bu; Huan Wang (Elsevier, 2019)
Diabetic nephropathy (DN) is one of the most common causes of end-stage renal disease (ESRD). Oxidative stress and inflammation have been documented to play important roles in the pathogenesis of DN. Daphnetin, a natural coumarin compound, possesses antioxidant and anti-inflammatory activities. However, the role of daphnetin in DN has not yet been investigated. The aim of the present study was to explore the function of daphnetin in DN and the underlying mechanism in vitro. Our results demonstrated that daphnetin alleviated cell proliferation induced by high glucose (HG) in human mesangial cells (MCs). Daphnetin strikingly reduced reactive oxygen species (ROS) and malonaldehyde (MDA) levels, and induced the superoxide dismutase (SOD) activity in HG-stimulated MCs. Besides, the production of TNF-α, IL-1β, IL-6, fibronectin (FN) and collagen IV (Col IV) was also inhibited by daphnetin in HG-stimulated MCs. In addition, daphnetin enhanced the expression of nuclear factor-erythroid 2-related factor 2 (Nrf2) and inhibited the levels of p-Akt and p-p65 in HG-stimulated MCs. The results indicated that daphnetin inhibited HG-induced oxidative stress, inflammatory response, and ECM accumulation in human MCs. The effect is partially mediated by Nrf2/keap1 and Akt/NF-κB pathways. The findings suggested that daphnetin might be a therapeutic or preventive agent for DN. Keywords: Diabetic nephropathy (DN), Daphnetin, High glucose (HG), Inflammatory response, Oxidative stress, Extracellular matrix (ECM) accumulation